Budget Participation, Leadership Style and Organizational Culture on Management Performance - M. Yusuf Alfian Rendra Anggoro KR; Yulianah Yulianah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The purpose of this study is to examine the relationship between budget participation, leadership style, organizational culture, and management performance. This study's population consisted of 98 institutional-level structural administrators at Muhammadiyah University in South Sulawesi. Using a straightforward random sampling technique, 30 respondents were sampled. Primary data obtained by disseminating questionnaires to all respondents is used as the data source. Techniques for data analysis using multiple regression and the SPSS program In addition, descriptive statistical analysis, classical assumption tests (normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test), and testing all hypotheses via partial test, simultaneous test, and determination coefficient test This study demonstrates that leadership style and organizational culture have a considerable impact on the management performance variables of all institutional-level structural officials at Muhammadiyah University in South Sulawesi. According to the findings of the analysis, leadership style is the most influential variable in efforts to enhance management performance as compared to organizational culture. This indicates that the company places a high priority on discipline so that all business operations can operate smoothly and efficiently. While the budget participation variable does not have a significant impact on the management performance variable of all institutional-level structural officials at Muhammadiyah University in South Sulawesi, it does have an impact on the variable of management performance.